Smart home control system design using internet of things based energy harvesting technology - Silalahi, Lukman Medriavin; Indrawan, Muhammad Rafi; Budiyanto, Setiyo; Hanafi, Dirman; Abdul Hamid, Abdul Hamid; Ronaldo, Davit (2024)
The problem in this research discusses home security control systems and energy harvesting technology based on the internet of things. Harvesting energy is a technology in storing electrical energy temporarily, the process starts from capturing sunlight energy. The objective of this research is to provide security for homeowners by facilitating fingerprints and PIN (Personal Identification Numbers) in entering the house, then in the event of a power outage, it activates the function of energy harvesting technology. The method is to design and analyze a prototype that combines the Raspberry Pi and its supporting components. The contribution of this research is to reduce the risk of theft or the risk of house fires due to electricity and overcome problems if the house is in a power outage. The novelty of this research is that the energy harvesting technology built on the Raspberry Pi as the main control and its supporting devices runs well in charging backups from solar panels with a length of 2 hours depending on the intensity of the light received. Then the Blynk application has a real-time response in monitoring electrical appliances at home.